Acute Pain Burden and Opioid Dose Requirements after Cesarean Delivery in Parturients with Preexisting Chronic Back Pain and Migraine - Ryu Komatsu; Michael G. Nash; Kenneth C. Ruth; William Harbour; Taylor M. Ziga; Shane Mandalia; Emily M. Dinges; Davin Singh; Hani El-Omrani; Joseph Reno; Brendan Carvalho; Laurent A. Bollag (Anesthesiology Research and Practice)
Introduction. Preexisting chronic pain has been reported to be a consistent risk factor for severe acute postoperative pain. However, each specific chronic pain condition has unique pathophysiology, and it is possible that the effect of each condition on postoperative pain is different. Methods. This is a retrospective cohort study of pregnant women with preexisting chronic pain conditions (i.e., migraine, chronic back pain, and the combination of migraine + chronic back pain), who underwent cesarean delivery. The effects of the three chronic pain conditions on time-weighted average (TWA) pain score (primary outcome) and opioid dose requirements in morphine milligram equivalents (MME) during postoperative 48 hours were compared. Results. The TWA pain score was similar in preexisting migraine and chronic back pain. Chronic back pain was associated with significantly greater opioid dose requirements than migraine (12.92 MME, 95% CI: 0.41 to 25.43, P=0.041). Preoperative opioid use (P<0.001) was associated with a greater TWA pain score. Preoperative opioid use (P<0.001), smoking (P=0.004), and lower postoperative ibuprofen dose (P=0.002) were associated with greater opioid dose requirements. Conclusions. Findings suggest women with chronic back pain and migraine do not report different postpartum pain intensities; however, women with preexisting chronic back pain required 13 MME greater opioid dose than those with migraine during 48 hours after cesarean delivery.